Economic and Environmental Efficiency Analysis: The Case Study of Intensive White-Leg Shrimp Farming in Phu Yen Province - Le Kim, Long (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper presents the theoretical background on economic and environmental efficiencies as well as the relationship between these two indicators based on the nutrient balance principle. The data envelopment analysis is adopted to calculate these indicators for intensive white-leg shrimp farming households in Phu Yen for the year of 2014. The results from 59 intensive shrimp household farms (24% of the population) in Phu Yen show that, on average, farming economic and environmental efficiencies are 69% and 78%, respectively. Improving technical efficiency can simultaneously improve both the farm’s economic and environmental efficiencies by an average of 10%. Differences in the ratios between market prices and the nutrient contents of shrimp feed and fingerlings have led to a trade-off between economic and environmental efficiencies with an average shadow cost of 1,858 million VND for 01 kg of nitrogen pollutant nutrient. Towards sustainable white-leg shrimp farming, policies on: (1) Technical training for this shrimp aquaculture; (2) subsidies for seeding research and production; and (3) pollution discharge tax or standards for treating shrimp farming wastes before discharging into the environment should be considered.
Keywords: Economic efficiency; Environmental efficiency; Technical efficiency; Intensive shrimp aquaculture